Applications of Green Inhibitors of Sugarcane Bagasse and Garcinia Kola Fruit Pod for Mild Steel Natural Gas Pipeline Corrosion Inhibition in Acidic Medium - Jemine, Teddy E.; Igbafe, Sylvia; Adeniyi, Adekunle Timisiriyu; IGBAFE, Anselm Iuebego (Computational And Experimental Research In Materials And Renewable Energy, 2024)
This study examined the effectiveness of sugarcane bagasse (SCB) and garcinia kola fruit pod (GKFP) extracts as green corrosion inhibitors on mild steel. Extracts of SCB and GKFP were obtained using ethanol in a solvent extraction and characterized physiochemically and phytochemically. Using central composite design (CCD) approach in design expert version 12, process variables of extract concentrations of 0.025 - 0.075 g per liter, exposure durations of 4 - 6 days and temperatures of 50 - 80 °C were varied for the evaluation of the gravimetric corrosion tests. Phytochemical analyses revealed the presence of alkaloids, flavonoids, glycosides, saponin, steroids, phenols, terpenoids, tannin and anthraquinones. FTIR analyses of the SCB and GKFP extracts indicated functional groups of phenols, hydroxyl, alcohols, carbonyl, esters, alkyl halides, aldehydes and alkenes. The best of the observed CCD findings on inhibition efficiencies were 92.11 and 90.20 % on SCB and GKFP extracts respectively with process conditions of inhibitor concentrations of 0.025 and 0.075 g/L of SCB and GKFP extracts respectively for temperature of 50 °C and exposure time 5 days. However, on overall analyses based on varying inhibitor concentrations, temperature range and duration of exposure, the optimal inhibition performance was 62.04 % with SCB and 64.35 % with GKFP. The most effective inhibitor is GKFP which yielded a higher inhibition efficiency under same operating conditions. bioactive compound acts as antioxidants in providing a reducing environment of the acidic reaction by which hydrogen ion in donated in the cause of the reaction. The investigation between the absence and presence of phytochemicals coupled with the components in both extracts from FTIR analyses revealed the significant participation of the bioactive agents of on the mild steel corrosion inhibition in acidic medium.Keywords: Sugarcane bagasse, Garcinia kola fruit pod, corrosion inhibitors, acidic medium mild steel